Arduino-Based Battery Voltage Monitoring and SMS Gateway - Muhammad Setiawan; Riky Dwi Puriyanto (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
This study aims to monitor the value of the voltage on the battery using a voltage sensor and using the State of Charge method to estimate the charged power of the VRLA battery remotely by utilizing SMS Gateway-based technology so that checking is no longer necessary. The results obtained are displayed on the smartphone in the form of an SMS. To determine the SOC in a 12V VRLA battery, it is calculated based on the number of each cell. VRLA 12V has 6 cells, each cell consisting of 2V to 2.4Volt. The capacity of a VRLA battery in 1 cell is declared 100% full at a voltage of 2.3 volts. So that data is obtained to determine the full percentage of the VRLA 12V 6 cell battery with a capacity of 7.2Ah, namely 13.8V. Experiments were carried out using solar panels, VRLA batteries, voltage sensors, Arduino UNO, and GSM SIM900A modules. This study succeeded in reading the measured voltage value with the sensor, and obtained an error value of 0.20 and a standard deviation of 0.02, and for the monitoring process to run smoothly without problems.